EditorialCardiac autonomic control in neurosurgery the example of trigemino-cardiac reflex - Schaller, Bernhard J.; Buchfelder, Michael; Filis, Andreas (Archives of Medical Science, 2007)
The trigemino-cardiac reflex (TCR) is defined as the sudden onset of parasympathetic dysrhythmia, sympathetic hypotension, apnoea or gastric hypermotility during stimulation of any of the sensory branches of the trigeminal nerve. In the present review, we summarize the knowledge about the TCR in relation to its two different ways of stimulation: (i) peripheral and (ii) central stimulation. We are the first to differentiate these two ways of occurrence of the TCR in our previous clinical work. From our studies, it seems that these differences are based on the varying autonomic control of the heart initiated either by peripheral or central stimulation. As despite the increasing clinical reports the physiological function of this brainstem reflex has not yet been fully explored, we give here new and important insights into this autonomic brainstem reflex. In addition, we try to give answers to the functional consequence of the different cardiac autonomic control of the TCR. By this physiological response, the adjustments of the systemic and cerebral circulations are initiated to divert blood to the brain or to increase blood flow within it. As a consequence, the striking age-related decline in the occurrence of the TCR seems to be the result of increased arterial stiffness. Our review gives therefore further insight into the potential brainstem circuit of the TCR, the most powerful autonomic reflex known in skull base surgery.